Preparation method of PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel
By modifying and crosslinking the Elosite nanotubes, PBA nanoparticles and polyethyleneimine are grown in situ to form a crosslinked composite aerogel, which solves the problem of easy residue of polyethyleneimine and difficulty in recycling of nanopowder materials, and achieves efficient adsorption of heavy metal ions.
Patent Information
- Application Number
- CN202510805101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-08-26
- Estimated Expiration
- 2045-06-17
AI Technical Summary
In the prior art, polyethyleneimine is prone to remain in water and the nanopowder material is difficult to recover, and Prussian blue analog nanoparticles are difficult to completely separate from the treatment system, resulting in poor adsorption effect of heavy metal ions.
Elolite nanotubes were modified by epoxy silane coupling agent, and PBA nanoparticles were grown in situ after grafting ethylenediamine, and crosslinked with polyethyleneimine to form a three-dimensional network structure. PBA nanoparticles were prepared in situ modified Elolite nanotube-polyethyleneimine crosslinked composite aerogel.
It realizes efficient adsorption of heavy metal ions, improves the structural stability and adsorption performance of the material, solves the problems of easy residues of polyethyleneimine and difficult to recover nanopowder materials, and improves the adsorption effect of heavy metal ions.
Smart Images

Figure CN120329603B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel. Background Art
[0002] Polyethyleneimine (PEI) molecular chains are rich in various active groups, including primary, secondary, and tertiary amines, which can bind to heavy metal ions through electrostatic interactions, coordination complexation, and other mechanisms. When used alone as an adsorbent, PEI can induce the precipitation of heavy metal ions to achieve separation, but due to its excellent water solubility, any PEI residues that are not effectively immobilized may be discharged with the solution.
[0003] Prussian blue analogues (PBA) have a unique zeolite-like microporous structure, and halloysite nanotubes (HNTs) are hollow tubular structures with a large specific surface area. Therefore, these materials also have good heavy metal adsorption capacity. However, due to the nanoscale particle size characteristics, it is difficult to completely separate them from the treatment system. Summary of the Invention
[0004] In response to the above-mentioned defects in the prior art, the present invention provides a method for preparing a PBA nanoparticle in situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel, which achieves efficient adsorption of heavy metal ions and solves the problems that polyethyleneimine easily remains in water and nanopowder materials are difficult to recycle.
[0005] The technical solution of the present invention is as follows: a method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel, comprising the following steps:
[0006] (1) Halloysite nanotubes were modified with an epoxy silane coupling agent to obtain epoxy-modified halloysite nanotubes;
[0007] (2) By utilizing the ring-opening reaction between epoxy groups and amino groups, ethylenediamine was grafted onto the surface of epoxylated halloysite nanotubes to obtain halloysite nanotubes rich in amino groups and hydroxyl groups;
[0008] (3) K4Fe(CN)6·3H2O and polyvinylpyrrolidone were stirred and dissolved in hydrogen chloride solution, and then halloysite nanotubes rich in amino groups and hydroxy groups were added and dispersed uniformly by ultrasonication to obtain PBA nanoparticles in situ modified halloysite nanotubes;
[0009] (4) Using 1,3-dichloropropanol as a cross-linking agent, an acid-binding agent was added, and the cross-linking reaction of halloysite nanotubes was in situ modified by polyethyleneimine and PBA nanoparticles. Finally, the reaction solution was freeze-dried, and then the residual acid-binding agent and its salts were removed by soaking and washing. It was then dried again to obtain PBA nanoparticles in situ modified halloysite nanotubes-polyethyleneimine cross-linked composite aerogel.
[0010] Furthermore, the step (1) specifically comprises ultrasonically dispersing the halloysite nanotubes in toluene, adding γ-glycidyloxypropyltrimethoxysilane to react, and filtering, washing, and drying after the reaction, wherein the mass ratio of the halloysite nanotubes to the γ-glycidyloxypropyltrimethoxysilane is 1:(0.5-2).
[0011] Furthermore, the reaction temperature in step (1) is 80-100° C., and the reaction time is 8-12 h.
[0012] Furthermore, the step (2) specifically comprises ultrasonically dispersing the epoxylated halloysite nanotubes in 1,4-dioxane, adding ethylenediamine to react, and filtering, washing, and drying after the reaction, wherein the mass ratio of the epoxylated halloysite nanotubes to ethylenediamine is 1:(0.4-0.8).
[0013] Furthermore, the reaction in step (2) is carried out under nitrogen protection, the reaction temperature is 70-90° C., and the reaction time is 4-6 h.
[0014] Furthermore, in step (3), the mass ratio of K4Fe(CN)6·3H2O, polyvinyl pyrrolidone and the halloysite nanotubes rich in amino groups and hydroxy groups is (0.2-0.4): (4-8): 1.
[0015] Furthermore, the reaction temperature in step (3) is 60-80° C., and the reaction time is 14-20 h.
[0016] Furthermore, the step (4) specifically comprises stirring and dissolving polyethyleneimine in deionized water, adding PBA nanoparticles to in-situ modify the halloysite nanotubes, ultrasonically dispersing the mixture uniformly, and then adding 1,3-dichloropropanol and an acid binding agent under nitrogen protection to carry out a cross-linking reaction, wherein the mass ratio of polyethyleneimine, PBA nanoparticles in-situ modifying the halloysite nanotubes, 1,3-dichloropropanol and the acid binding agent is (3-7):1:(0.4-0.8):(1.5-3).
[0017] Furthermore, the acid binding agent is triethylamine or pyridine.
[0018] Furthermore, in step (4), the cross-linking reaction temperature is 60 to 80° C., the reaction time is 8 to 12 h, and the freeze-drying is to freeze-dry the reaction solution at -50 to -40° C. for 30 to 50 h.
[0019] The present invention first modifies halloysite nanotubes (HNTs) using an epoxysilane coupling agent to produce epoxy-modified HNTs. Subsequently, ethylenediamine is used to modify the epoxy-modified HNTs, enriching their surfaces with amino and hydroxyl functional groups, based on the ring-opening reaction between epoxy and amino groups. Furthermore, Prussian blue analog (PBA) nanoparticles are in situ grown on the surface of the HNTs, utilizing the coordination chemistry between hexacyanoferrate ions and amino groups, to construct PBA nanoparticle-modified halloysite nanotubes (PBA@HNTs). Finally, using 1,3-dichloropropanol as a crosslinker, a strong chemical bonding network is formed through crosslinking between the uncoordinated active functional groups on the surface of the PBA nanoparticle-modified halloysite nanotubes and the abundant amino groups on the polyethyleneimine (PEI) molecular chains. After freeze-drying and impurity removal, a cross-linked composite aerogel material with both high adsorption performance and excellent structural stability is obtained.
[0020] The advantages of the present invention compared with the prior art are:
[0021] (1) The present invention in situ grows PBA nanoparticles on the surface of halloysite nanotubes and then crosslinks them with PEI molecular chains to form a three-dimensional network structure, achieving a multi-level composite of inorganic nanotubes, metal organic frameworks, and organic polymers. The components have excellent interfacial bonding, which can fully utilize the synergistic enhancement and deep integration of the three in adsorption performance. At the same time, using 1,3-dichloropropanol as a crosslinking agent introduces more hydroxyl groups with adsorption activity, thereby effectively improving the material's adsorption performance for heavy metal ions.
[0022] (2) The present invention modifies the surface of halloysite nanotubes with amino and hydroxyl groups, effectively increasing the number of coordination sites and achieving the firm in-situ growth of PBA nanoparticles on the surface of halloysite nanotubes. At the same time, the PBA nanoparticles are in-situ modified into the halloysite nanotubes and chemically bonded to the PEI molecular chains through a cross-linking reaction, significantly improving the structural stability of the aerogel and effectively solving the problem of polyethyleneimine easily remaining in the solution and the difficulty of recovering and reusing the nanopowder material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of the in-situ modification of halloysite nanotubes by PBA nanoparticles prepared in Example 1.
[0024] Figure 2 This is an SEM image of the PBA nanoparticle in situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel prepared in Example 1. DETAILED DESCRIPTION
[0025] The present invention will be further described below with reference to the examples, but are not intended to limit the present invention.
[0026] Example 1
[0027] A method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel comprises the following steps:
[0028] (1) Disperse 1g of halloysite nanotubes (Xianfeng Nano, CAS No.: 1332-58-7, Product No.: 103763) in toluene by ultrasonication, and add 0.5g of γ -glycidyloxypropyltrimethoxysilane, stirred at 80 ° C for 12 hours, filtered, washed and dried to obtain epoxy HNTs.
[0029] (2) 1 g of the prepared epoxylated HNTs was ultrasonically dispersed in 1,4-dioxane, 0.4 g of ethylenediamine was added, and the reaction solution was stirred at 70 °C under nitrogen protection for 6 h. After the reaction, it was filtered, washed, and dried to obtain HNTs rich in amino and hydroxyl groups.
[0030] (3) 0.2 g K4Fe(CN)6·3H2O and 4 g polyvinylpyrrolidone were stirred and dissolved in hydrogen chloride solution (0.1 M), and then 1 g of the prepared HNTs rich in amino and hydroxyl groups was added and dispersed evenly by ultrasonication. The mixture was stirred and grown in situ at 60 °C for 20 h to obtain PBA@HNTs. The SEM image of the PBA@HNTs is shown in FIG. Figure 1 As shown, it can be seen that PBA nanoparticles with relatively regular shapes were generated in situ on the surface of HNTs.
[0031] (4) 3 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, 1 g of the prepared PBA@HNTs was added, and after ultrasonic dispersion, 0.4 g of 1,3-dichloropropanol and 1.5 g of triethylamine were added under nitrogen protection at 60 o After the cross-linking reaction for 12 h, the reaction solution was heated at -40 o C for 50 h, and then the sample was taken out and immersed in ethanol for 12 h, and the ethanol was changed every 3 h. The sample was taken out and dried to obtain the PBA nanoparticle in situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel. The SEM image is shown in FIG. Figure 2 As shown, it can be seen that it has a rich pore structure.
[0032] The adsorption performance experiment of the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel prepared in Example 1 is as follows:
[0033] Prepare 100 mL of a 100 mg / L aqueous solution of lead ions (lead nitrate as a reagent) in a flask, adjust the pH of the solution to 7 with 0.1 M NaOH, add the prepared PBA@HNTs-PEI cross-linked composite aerogel, and then o C constant temperature oscillator, adsorption at 200 rpm for 3 hours. After adsorption, the supernatant was taken and the lead ion concentration in the supernatant was determined by ICP-OES. The adsorption amount of lead ions by the adsorbent material was calculated by the following formula ( Q , mg / g), and the results are listed in Table 1.
[0034] Q =( C 0 - C t ) V / M
[0035] Q is the adsorption capacity (mg / g); C 0 is the initial concentration of heavy metal ions (mg / L); C t is the concentration of heavy metal ions after adsorption (mg / L); V is the volume of the solution (L); M is the mass of the adsorbent (g).
[0036] Example 2
[0037] A method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel comprises the following steps:
[0038] (1) Disperse 1g of halloysite nanotubes (Xianfeng Nano, CAS No.: 1332-58-7, Product No.: 103763) in toluene by ultrasonication, and add 1.25g of γ -glycidyloxypropyltrimethoxysilane, stirred at 90 ° C for 10 hours, filtered, washed and dried to obtain epoxy HNTs;
[0039] (2) 1 g of the prepared epoxylated HNTs was ultrasonically dispersed in 1,4-dioxane, 0.6 g of ethylenediamine was added, and the reaction solution was stirred at 80 °C under nitrogen protection for 5 h. After the reaction, the solution was filtered, washed, and dried to obtain HNTs rich in amino and hydroxyl groups.
[0040] (3) 0.3 g of K4Fe(CN)6·3H2O and 6 g of polyvinylpyrrolidone were stirred and dissolved in a hydrogen chloride solution (0.1 M), and then 1 g of the prepared HNTs rich in amino and hydroxyl groups was added and ultrasonically dispersed uniformly. The mixture was stirred at 70 °C and grown in situ for 17 h to obtain PBA@HNTs.
[0041] (4) 5 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, and 1 g of the prepared PBA@HNTs was added. After ultrasonic dispersion, 0.6 g of 1,3-dichloropropanol and 2.25 g of pyridine were added under nitrogen protection. After the cross-linking reaction was carried out at 70 °C for 10 h, the reaction solution was freeze-dried at -45 °C for 40 h. The sample was taken out and soaked in warm water at 40 °C for 10 h, and the water was changed every 2 h. The sample was taken out and dried to obtain PBA nanoparticles in situ modified halloysite nanotubes-polyethyleneimine cross-linked composite aerogel. Its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.
[0042] Example 3
[0043] A method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel comprises the following steps:
[0044] (1) Ultrasonic dispersion of 1g of halloysite nanotubes (Xianfeng Nano, CAS No.: 1332-58-7, Product No.: 103763) in toluene was added with 2g of γ -glycidyloxypropyltrimethoxysilane, stirred at 100 ° C for 8 hours, filtered, washed and dried to obtain epoxy HNTs.
[0045] (2) 1 g of the prepared epoxylated HNTs was ultrasonically dispersed in 1,4-dioxane, and 0.8 g of ethylenediamine was added. The reaction solution was stirred at 90 °C under nitrogen protection for 4 h. After the reaction, it was filtered, washed, and dried to obtain HNTs rich in amino groups and hydroxyl groups.
[0046] (3) 0.4 g K4Fe(CN)6·3H2O and 8 g polyvinylpyrrolidone were stirred and dissolved in hydrogen chloride solution (0.1 M), and then 1 g of the prepared HNTs rich in amino and hydroxyl groups was added and ultrasonically dispersed uniformly. The mixture was stirred at 80 °C and grown in situ for 14 h to obtain PBA@HNTs.
[0047] (4) 7 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, and 1 g of the prepared PBA@HNTs was added. After ultrasonic dispersion, 0.8 g of 1,3-dichloropropanol and 3 g of triethylamine were added under nitrogen protection. After cross-linking reaction at 80 °C for 8 h, the reaction solution was freeze-dried at -50 °C for 30 h. The sample was taken out and soaked in ethanol for 8 h, and the ethanol was changed every 1 h. The sample was taken out and dried to obtain PBA nanoparticles in situ modified halloysite nanotubes-polyethyleneimine cross-linked composite aerogel. Its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.
[0048] Comparative Example 1
[0049] 3 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, 1 g of pristine HNTs was added, and after ultrasonic dispersion, the solution was freeze-dried at -40°C for 50 h to obtain an HNTs-PEI composite aerogel. The adsorption properties of the aerogel were measured according to the adsorption properties experiment of the product in Example 1. The results are listed in Table 1.
[0050] Comparative Example 2
[0051] 3 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, and 1 g of PBA@HNTs (prepared according to steps (1), (2), and (3) of Example 1) was added. After ultrasonic dispersion, the solution was freeze-dried at -40°C for 50 h to obtain PBA@HNTs-PEI composite aerogel. Its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.
[0052] Comparative Example 3
[0053] (1) 0.2 g K4Fe(CN)6·3H2O and 4 g polyvinylpyrrolidone were stirred and dissolved in hydrogen chloride solution (0.1 M), and then 1 g of original HNTs was added and dispersed evenly by ultrasonication. The mixture was stirred and grown in situ at 60 °C for 20 h to obtain PBA-modified halloysite nanotubes.
[0054] (2) 3 g of polyethyleneimine (average molecular weight 600) was stirred and dissolved in deionized water, and 1 g of the prepared PBA-modified halloysite nanotubes was added. After ultrasonic dispersion, 0.4 g of 1,3-dichloropropanol and 1.5 g of triethylamine were added under nitrogen protection. After the cross-linking reaction was carried out at 60 ° C for 12 h, the reaction solution was freeze-dried at -40 ° C for 50 h. The sample was taken out and soaked in ethanol for 12 h, and the ethanol was changed every 3 h. The sample was taken out and dried to obtain a cross-linked composite aerogel. Its adsorption performance was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.
[0055] Table 1 Adsorption capacity of lead ions by aerogels prepared in Examples 1-3 and Comparative Examples 1-3
[0056]
[0057] The results show that the in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogels prepared in the present invention with PBA nanoparticles achieve effective cross-linking between the filler and the resin matrix, optimizing the aerogel's pore structure while also introducing more active hydroxyl groups with adsorption properties and enhancing interfacial bonding. Furthermore, due to the excellent interfacial bonding, a perfect combination and synergistic enhancement of the adsorption properties of HNTs, PBA nanoparticles, and PEI are achieved. Consequently, the prepared aerogel exhibits excellent adsorption performance for lead ions, with a maximum adsorption capacity of 351 mg / g.
[0058] The aerogels produced in Comparative Examples 1-3 cannot compare to the cross-linked aerogels produced in Examples in terms of porosity, interfacial bonding, number of active groups, and synergistic enhancement. Consequently, their adsorption performance is far inferior to that of Examples. In particular, the comparison between Examples and Comparative Example 2 fully demonstrates the importance of cross-linking modification, while the comparison between Examples and Comparative Example 3 fully demonstrates the importance of pre-amino group enrichment and hydroxylation of the HNT surface.
Claims
1. A method for preparing a PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel, characterized in that: The following steps are involved: (1) Halloysite nanotubes were modified with an epoxy silane coupling agent to obtain epoxy-modified halloysite nanotubes; (2) By utilizing the ring-opening reaction between epoxy groups and amino groups, ethylenediamine was grafted onto the surface of epoxylated halloysite nanotubes to obtain halloysite nanotubes rich in amino groups and hydroxyl groups; (3) K4Fe(CN)6·3H2O and polyvinylpyrrolidone were stirred and dissolved in hydrogen chloride solution, and then halloysite nanotubes rich in amino groups and hydroxy groups were added and dispersed uniformly by ultrasonication to obtain PBA nanoparticles in situ modified halloysite nanotubes; (4) Using 1,3-dichloropropanol as a cross-linking agent, an acid-binding agent was added, and the cross-linking reaction of halloysite nanotubes was in situ modified by polyethyleneimine and PBA nanoparticles. Finally, the reaction solution was freeze-dried, and then the residual acid-binding agent and its salts were removed by soaking and washing. It was then dried again to obtain PBA nanoparticles in situ modified halloysite nanotubes-polyethyleneimine cross-linked composite aerogel.
2. The method for preparing the PBA nanoparticle in situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 1, characterized in that: The step (1) specifically comprises ultrasonically dispersing the halloysite nanotubes in toluene, adding γ-glycidyloxypropyltrimethoxysilane to react, and filtering, washing, and drying after the reaction, wherein the mass ratio of the halloysite nanotubes to the γ-glycidyloxypropyltrimethoxysilane is 1:(0.5-2).
3. The method for preparing the PBA nanoparticle in situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 2, characterized in that: The reaction temperature in step (1) is 80-100° C., and the reaction time is 8-12 h.
4. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 1, characterized in that: The step (2) specifically comprises ultrasonically dispersing the epoxylated halloysite nanotubes in 1,4-dioxane, adding ethylenediamine to react, and then filtering, washing, and drying after the reaction, wherein the mass ratio of the epoxylated halloysite nanotubes to ethylenediamine is 1:(0.4-0.8).
5. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 4, characterized in that: The reaction in step (2) is carried out under nitrogen protection, the reaction temperature is 70-90° C., and the reaction time is 4-6 h.
6. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 1, characterized in that: In the step (3), the mass ratio of K4Fe(CN)6·3H2O, polyvinyl pyrrolidone and the halloysite nanotubes rich in amino groups and hydroxy groups is (0.2-0.4): (4-8):
1.
7. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 6, characterized in that: The reaction temperature in step (3) is 60-80° C. and the reaction time is 14-20 h.
8. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 1, characterized in that: The step (4) specifically comprises stirring and dissolving polyethyleneimine in deionized water, adding PBA nanoparticles to in-situ modify the halloysite nanotubes, uniformly dispersing by ultrasonication, and then adding 1,3-dichloropropanol and an acid binding agent under nitrogen protection to carry out a cross-linking reaction, wherein the mass ratio of polyethyleneimine, PBA nanoparticles in-situ modifying the halloysite nanotubes, 1,3-dichloropropanol and the acid binding agent is (3-7):1:(0.4-0.8):(1.5-3).
9. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 8, characterized in that: The acid binding agent is triethylamine or pyridine.
10. The method for preparing the PBA nanoparticle in-situ modified halloysite nanotube-polyethyleneimine cross-linked composite aerogel according to claim 8, characterized in that: In the step (4), the cross-linking reaction temperature is 60 to 80° C., the reaction time is 8 to 12 hours, and the freeze drying is to freeze-dry the reaction solution at -50 to -40° C. for 30 to 50 hours.
Citation Information
Patent Citations
Halloysite nanotube / epoxy nanocomposite
CN105860435A
Halloysite / polyvinyl alcohol aerogel composite material as well as preparation method and application thereof
CN115487757A